Association between Pap smear screening and job stress in Taiwanese nurses. (February 2016) - Su, Shiang-Yuan; Chiou, Shu-Ti; Huang, Nicole; Huang, Chiu-Mieh; Chiang, Jen-Huai; Chien, Li-Yin
Abstract: Purpose: Nursing is a professional job characterized by high stress. Stress could be associated with less practice of health promoting behaviors; however, no study has investigated the relationship between job stress and health screening behaviors among nurses. This study aimed to describe the rate of Pap smears in hospital nurses and examine the effects of job stress on receiving a Pap smear. Methods: This study was a cross-sectional survey. The study participants were 30, 681 full-time female nurses who were at least 30 years of age working in 100 hospitals across Taiwan. The study participants filled out an anonymous structured questionnaire from May to July, 2011. The outcome variable was having a Pap test during the previous 3 years. The level of stress was measured by a 19-item scale, with higher scores indicating higher stress levels. Results: About 62.4% of the nurses had a Pap smear during the previous three years. Each point increase in the stress score decreased the likelihood of Pap smears (OR = .997, 95% CI: .995–.999), after adjustment for participant characteristics, health status, health behaviors, and hospital characteristics. Conclusion: Despite more knowledge and higher accessibility, nurses were less likely to have Pap smear screening than the general population. A higher level of job stress was associated with a lower likelihood of having a Pap smear. Hospital administrators could help decrease work-related stress and improve stress adaption among nurses in order to improve their health screening behaviors. Highlights: Hospital nurses had a lower rate of Pap smears than the general population. Job stress was negatively associated with receiving a Pap smear among nurses. Hospital administrators should help decrease work-related stress among nurses.